The Relationship between the Timing of Complementary Feeding and Maternal Knowledge of Responsive Feeding and the Incidence of Stunting in Children Aged 6-24 Months - Hidayatul Waqiyah; Arie Maineny; Nurfatimah Nurfatimah (Poltekkes Kemenkes Palu, 2023)
In 2021, the prevalence of stunting among toddlers in Wani Primary Health Care (Puskesmas) was still high at 18.2%. Delayed introduction of complementary feeding (MP-ASI) and inappropriate feeding practices, such as lack of responsive feeding, contribute to the occurrence of stunting. The objective of this study was to investigate the relationship between the timing of MP-ASI introduction and maternal knowledge of responsive feeding with the occurrence of stunting among children aged 6 to 24 months. This research employed a cross-sectional design using quantitative analytic observational methods. Simple random sampling was used to select the sample, and data were collected through questionnaire surveys from 126 mothers with children between the ages of 6 and 24 months. The study was conducted in the communities of Nupa Bomba, Bale, and Wani Lumbumpetigo, all located within the working area of Wani Primary Health Care. The results showed that 80.2% of the timing of MP-ASI introduction was inappropriate, and 62.7% of the mothers had insufficient knowledge of responsive feeding. The chi-square test revealed a significant association between the timing of MP-ASI introduction and the occurrence of stunting (p value = 0.047, OR = 0.290), as well as between the occurrence of stunting and maternal knowledge of responsive feeding (p value = 0.008, OR = 0.298). In conclusion, there is a relationship between the occurrence of stunting and the timing of MP-ASI introduction, as well as maternal knowledge of responsive feeding. It is recommended to enhance parental knowledge and attitudes and prevent stunting by providing nutrition education through counseling on proper complementary feeding and responsible childcare practices. This study highlights the importance of improving education and support for mothers to prevent stunting.